2009
DOI: 10.1111/j.1440-1746.2009.05782.x
|View full text |Cite
|
Sign up to set email alerts
|

One‐hour fast for water and six‐hour fast for solids prior to endoscopy provides good endoscopic vision and results in minimum patient discomfort

Abstract: A 6-h fast for solids and a 1-h fast for water prior to UGIE gives good endoscopic vision, and causes minimum patient discomfort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 10 publications
2
25
0
2
Order By: Relevance
“…This confirms the results of an earlier study done more than 10 years ago 12,13 . Our study was designed mainly to assess the quality of endoscopic vision and patient discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…This confirms the results of an earlier study done more than 10 years ago 12,13 . Our study was designed mainly to assess the quality of endoscopic vision and patient discomfort.…”
Section: Discussionsupporting
confidence: 92%
“…32 Similar results have been obtained for patients undergoing upper gastrointestinal endoscopy. 5,33 Findings from other studies suggest that fasting may not be necessary for computed tomography with intravenous contrast, 34 abdominal ultrasonography, 8 coronary intervention, 9 or conscious sedation. 35 Interestingly, a small study found that patients may be able to eat lunch even before an afternoon colonoscopy without compromising the quality of the study, as long as the bowels have been adequately prepared.…”
Section: Discussionmentioning
confidence: 97%
“…The ingestion of clear fluids containing carbohydrates few hours before elective procedures has been shown to be safe, resulting in similar volumes of gastric residua without pH changes in comparison to more prolonged fasting periods [17-19]. For upper GI endoscopy, at least two studies have looked to this question, showing good visibility and improved comfort with the ingestion of water just before endoscopy [20,21]. However, further evidence is still needed in order to change the paradigm of prolonged fasting before upper GI endoscopy.…”
Section: Introductionmentioning
confidence: 99%